2009
DOI: 10.1002/hon.892
|View full text |Cite
|
Sign up to set email alerts
|

KHSV EBV post‐transplant effusion lymphoma with plasmablastic features: variant of primary effusion lymphoma?

Abstract: Primary effusion lymphoma (PEL) is a rare type of B-cell non-Hodgkin lymphoma (NHL), which predominantly occurs in HIV-infected individuals, and is pathogenetically linked with Kaposi sarcoma (KS)-associated herpes virus/human herpes virus-8 (KSHV/HHV-8) infection with or without evidence of Epstein-Barr virus (EBV) co-infection. Although uncommon, PELs have been reported in immunocompetent patients and recipients of solid organ allografts. Rare cases of KSHV(-) EBV(+) post-transplant effusion lymphomas resemb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…Lymphomatous ascites has been described in post-LT patients; however, the cases of Burkitt's lymphoma involved intra-abdominal/pelvic masses [ 2 ]. There have also been rare cases of PTLD that mimic primary effusion lymphoma in EBV (−) and HHV8 (−) patients [ 12 ]. In a gene analysis profile study, the impact of HHV8 and EBV on cellular gene expression and pathogenesis of lymphomatous effusions was evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Lymphomatous ascites has been described in post-LT patients; however, the cases of Burkitt's lymphoma involved intra-abdominal/pelvic masses [ 2 ]. There have also been rare cases of PTLD that mimic primary effusion lymphoma in EBV (−) and HHV8 (−) patients [ 12 ]. In a gene analysis profile study, the impact of HHV8 and EBV on cellular gene expression and pathogenesis of lymphomatous effusions was evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…PTLDs often present with widely disseminated disease, including up to 13% of patients with central nervous system involvement at the time of diagnosis . In addition to rare reports of post‐transplant primary effusion lymphomas, some authors have suggested that the presence of a PTLD in serous effusions is an adverse prognostic indicator similar to what has been described in other lymphomas such as DLBCL . The literature evaluating PTLDs in exfoliative cytology specimens, however, is limited, with the 2 largest series (from 18 to 25 years ago) including no more than 9 cases diagnostic of PTLDs and with extremely limited ancillary studies described .…”
Section: Discussionmentioning
confidence: 99%
“…The cytologic assessment of PTLDs has received much less attention than the evaluation of histopathologic specimens despite a growing literature on the use of flow cytometry, molecular, and cytogenetic fluorescence in situ hybridization (FISH) techniques to improve the diagnostic accuracy of cytopathologic evaluations of lymphoid proliferations in fine‐needle aspiration and exfoliative fluid specimens . Although some authors have also proposed that fine‐needle aspiration is a highly sensitive and specific diagnostic tool for the initial evaluation of transplant patients suspected to have PTLDs, the cytomorphologic features of PTLDs involving exfoliative cytology specimens taken in an attempt either to diagnose a PTLD or to assess whether a known PTLD is disseminated are less well characterized . Previous studies evaluating PTLDs in exfoliative cytology specimens consist primarily of case reports and small series, and most of the described cases have had cytologic features compatible with the more easily recognized M‐PTLD .…”
Section: Introductionmentioning
confidence: 99%
“…By in situ hybridization, EBV is detected in varying percentages, with up to 78% of cases reported by some authors . The expression of HHV8, which is detected in 100% of cases, is essential for a correct diagnosis of primary effusion lymphoma, although rare cases negative for both EBV and HHV8 have been reported . The positive staining of the nuclei of neoplastic cells for HHV8‐associated latent protein (LANA) shows a characteristic pattern of multiple nuclear dots.…”
Section: Discussionmentioning
confidence: 99%
“…24 The expression of HHV8, which is detected in 100% of cases, is essential for a correct diagnosis of primary effusion lymphoma, although rare cases negative for both EBV and HHV8 have been reported. 25 The positive staining of the nuclei of neoplastic cells for HHV8-associated latent protein (LANA) shows a characteristic pattern of multiple nuclear dots. Therefore, analysis of viral infection is of primary importance in establishing the diagnosis of this solid variant of primary effusion lymphoma.…”
Section: Discussionmentioning
confidence: 99%